2021
DOI: 10.3390/earth2030029
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Changes in Sedimentation and Source Provenance in East African Hydropower Reservoirs: A Case Study of Nyumba ya Mungu in Tanzania

Abstract: This study aimed to reconstruct the sedimentation rates over time and identify the changing sources of sediment in a major hydropower reservoir in Tanzania, the Nyumba ya Mungu (NYM). Fallout 210Pb measurements were used to estimate age of sediment deposits and broad changes in sedimentation rates were reconstructed. Sedimentation peaks were cross referenced to geochemical profiles of allogenic and autogenic elemental constituents of the sediment column to confirm a causal link. Finally, geochemical fingerprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…The mean rate of soil loss by water in Tanzania is 4.1 and 10.1 tha −1 yr −1 for all land cover classes and per cropland, respectively [6]. The sedimentation rate in the catchment's (the Nyumba ya Mungu) hydropower reservoir is averagely 1.5 g cm −2 yr −1 [7]. Studies by Vanmaercke, Poesen, Broeck, and Nyssen [8] revealed that the sediment yield in East Africa typically range between 100 to 1000 t/km 2 /year.…”
Section: Introductionmentioning
confidence: 98%
“…The mean rate of soil loss by water in Tanzania is 4.1 and 10.1 tha −1 yr −1 for all land cover classes and per cropland, respectively [6]. The sedimentation rate in the catchment's (the Nyumba ya Mungu) hydropower reservoir is averagely 1.5 g cm −2 yr −1 [7]. Studies by Vanmaercke, Poesen, Broeck, and Nyssen [8] revealed that the sediment yield in East Africa typically range between 100 to 1000 t/km 2 /year.…”
Section: Introductionmentioning
confidence: 98%
“…In the Lake Victoria Basin in Northern Tanzania, an increasing demand for food and energy from a growing population has led to an expanse in agricultural areas and widespread deforestation [19,20]. The pressure has even led to alterations in the catchment's agricultural practices, shifting from traditional mixed perennial agriculture toward more intensive cropping with minimal devotion to soil and water conservation [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The Simiyu catchment has experienced flooding in the last decades, which has impacted both human safety and agricultural yields [31]. In 2007, the study area received intensive rains that culminated into floods, eventually resulting in the injury, damage and loss of life and assets, local infrastructure distraction, and forced relocation [20,32,33]. Studies in the area assume that the increased flood peaks are caused by increasing settlements that have led to deforestation, wetland degradation and increased impervious surfaces [34,35].…”
Section: Introductionmentioning
confidence: 99%